(untitled) - Lindop, Christine (Oxford, 2010)
Once 'green' was just a colour. Now we use it to talk about a way of looking at our world and thinking about the environment. But how green is our planet today? From nuclear power plants to Nemo the clownfish, from polar bears to pesticides, from Greenpeace to global warming, this book brings together many different stories that have made environmental history. Read it, and perhaps you too can help to make our planet greener!
Keywords: English language,Reading comprehension,Đọc hiểu; Textbooks for foreign speakers.,Problems, exercises, etc.,Câu hỏi và bài tập